The tigers of Trengganu - Locke, Arthur (Monographs of the Malaysian Branch, Royal Asiatic Society, 1993)
Tigers are seldom seen in Peninsular Malaysia today, except in Zoos. But in 1949, tigers were still numerous in remote rural areas, and in South Trengganu they were killing cattle and even children. It was fortunate for the villagers that Mr. A. Locke of the Malayan Civil Service was posted to Kemaman to help to administer the southern half of the state. For two years, from 1949 to 1951, Mr. Locke in his spare time, in the dark tracked down and shot twenty-two tigers, often seated on a precarious little platform up a jungle tree, only twleve feet above the ground. He later wrote an account of his experiences illustrated with numerous photographs of the tigers which he had shot, and it quickly became a 'best seller'.